2021
DOI: 10.1371/journal.pone.0245810
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum 4HNE plus decreased serum thioredoxin: Unique feature and implications for acute exacerbation of chronic obstructive pulmonary disease

Abstract: Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is a global problem with high mortality. Its pathogenesis is not fully understood. To reveal new serum feature of AECOPD and their potential implications, we have analyzed 180 serum samples, and found that in the serum of AECOPD patients, 4-hydroxy-2-nonenal (4HNE)-protein adducts are dynamically increased as partial pressure of oxygen (PaO2) drops, which is accompanied by progressively decreasing thioredoxin reductase (TrxR1) and thioredoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In addition to the negative effects of oxidative stress in the lungs, increased systemic ROS are detected, especially during COPD exacerbations, which are indicated by the increase in lipid peroxidation products and 4-hydroxynonenal (4-HNE) in the serum [ 103 , 104 ]. Although the detailed mechanisms underlying the comorbidities of COPD remain to be elucidated, ROS in combination with systemic inflammation are involved in the pathology of extrapulmonary manifestations, such as osteoporosis and skeletal muscle weakness, in patients with COPD [ 105 ].…”
Section: Impaired Redox Regulation In Aging and Patients With Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the negative effects of oxidative stress in the lungs, increased systemic ROS are detected, especially during COPD exacerbations, which are indicated by the increase in lipid peroxidation products and 4-hydroxynonenal (4-HNE) in the serum [ 103 , 104 ]. Although the detailed mechanisms underlying the comorbidities of COPD remain to be elucidated, ROS in combination with systemic inflammation are involved in the pathology of extrapulmonary manifestations, such as osteoporosis and skeletal muscle weakness, in patients with COPD [ 105 ].…”
Section: Impaired Redox Regulation In Aging and Patients With Copdmentioning
confidence: 99%
“…These results suggest that the body attempts to neutralize excessive oxidative stress in COPD lungs by producing TRX. On the other hand, serum TRX levels are significantly decreased during acute exacerbations in patients with COPD accompanied by an increase in 4-hydroxynonenal (4-HNE) in serum [ 104 ], which suggests that systemic detrimental oxidative stress occurs by overwhelming the protective effects of TRX during acute exacerbations. Thus, these results suggest that tissue TRX levels are a good noninvasive marker of oxidative stress in patients with COPD and can be used to stratify patients with COPD for the identification of patient subpopulations who will benefit from antioxidant-targeting treatments.…”
Section: Antioxidant Drugsmentioning
confidence: 99%
“…Txn1 is a member of thioredoxins (Trxs) family and has been characterized as a guard of the intracellular redox state and antioxidants [7]. Previous studies have shown that Txn1 is involved in liver cancer, myocardial ischemia, pulmonary fibrosis, and brain diseases such as intracerebral infarction and Alzheimer's disease [8][9][10][11][12]. It mainly relieves oxidative stress in the central nervous system through Nrf2/Txn1/TXNIP [11] and other signal pathways, thus reducing brain injury.…”
Section: Introductionmentioning
confidence: 99%